Pelaksanaan Pembelajaran Daring di SD Negeri Caturtunggal 1 Depok Sleman DIY pada Masa Pandemi Covid-19 - Adhy Putri Rilianti; Anisa Saraswati (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2021)
The Covid-19 pandemic has affected the world of education, which previously had face-to-face learning to online or online learning. This research aimed to describe planning, implementation, and evaluation of online learning in SDN Caturtunggal 1 Depok, Sleman, DIY. This is qualitative research. Data was collected by observation and interview with teachers and students. Data was analyzed by triangulation to get the conclusion. This research resulted in three conclusions. First, online learning planning was done through designing lesson plans, designing online teaching materials, and preparing online learning platforms. Second, the implementation of online learning was initially carried out full-online then hybrid-learning. The learning methods that teachers often use were lectures, questions and answers, and project-based learning. Third, online learning evaluation was initially done manually, photographed, and sent via Whatsapp. As students' skills develop, student work was sent through google form. For summative assessment, teachers often use Quizizz. The biggest obstacle in implementing online learning was the device, namely the availability of mobile phones and laptops because 75% of students do not have their own devices. Other constraints are network instability, internet quota, students' level of understanding, and students' level of honesty.